Kinetika kalsinasi seria zirkonia dari proses gelasi eksternal - Fera Wahyuningsih; Wahyudi Budi Sediawan; Teguh Ariyanto; Sri Widiyati (Jurnal Rekayasa Proses, 2016)
Calcination process is one of the important steps in the synthesis of nuclear fuel particles for High Temperature Reactor (HTR). In this work, the calcination process of Ceria-Stabilized Zirconia (CSZ) was carried out. The aims of the study are to study the kinetic modelling of calcination process of CSZ kernel, to determine the suitable operation condition, and to observe physical characters of the calcined material. The feed of calcination process was material prepared by an external gelation. The calcination was conducted from room temperature to 500 oC with heating rate of 1 and 2 °C/min. CSZ kernel per grain was weighted and the diameter was measured during calcination process, hence determining the weight loss and size change. The results showed that there was a weight loss of kernel during calcination process. When the weight of grain reached a constant value, the process of calcination was considered complete.